Agroforestry Dynamics Among Different Landholding Farmers in Vrishabhavathi Basin, Karnataka - Poornima M; B.C. Nagaraja (Annals of Arid Zone, 2024)
The agroforestry emerges as effective adaptation strategy to combat climate change and restrict urban expansion in semi-arid regions of India. The present study aims at understanding the spatial distribution of trees and agroforestry characteristics among small, medium and large landholding farmers around Vrishabhavathi river stretch in peri-urban region of Bangalore. A total of 34379 trees and 41 tree species was recorded in 679.2 ha area belonging to 100 farmers. The major proportion of trees (85 %), belonged to commercial plantation crops such as Areca nut and Coconut. The data indicated significant linear correlation between landholding category and tree density, suggesting that increase in number of trees with increase in land size. Analysis on girth class distribution across landholding indicated that concentration of smaller-sized trees in small and medium landholders, suggesting subsistence-oriented agroforestry practices. An intermediate agroforestry is largely practiced in all three landholding categories, where perennial commercial plantation is done along with food and fodder crops. The study provides insight on agroforestry for farmers, urban planners, agriculture and horticulture functionaries to foster sustainable practices in polluted urban fringe.